Evolutionary analysis of the DHHCs in Saccharinae - Hao Wen; Xinyu Liu; Xueting Zhao; Tingting Zhao; Cuilian Feng; Hailong Chang; Jungang Wang; Jishan Lin (Scientific Reports)
Abstract The DHHC domain genes are crucial for protein lipid modification, a key post-translational modification influencing membrane targeting, subcellular trafficking, and protein function. Despite their significance, the DHHC gene family in Saccharinae remains understudied. Here, we identified 32 (110 alleles), 28, 53, and 48 DHHC genes in Saccharum spontaneum Np-X, Erianthus rufipilus, Miscanthus sinensis, and Miscanthus lutarioriparius, respectively. Collinearity analysis uncovered the loss of two M. lutarioriparius genes, homologues of EruDHHC1C and EruDHHC3A. Phylogenetic and classification analyses categorized DHHC family members into six subgroups (A-F). Ka/Ks ratio analysis indicated that gene duplication in these species was primarily driven by whole-genome duplication (WGD) and dispersed duplication (DSD), with DHHC genes evolving under strong purifying selection. Gene expression and trait correlation analysis revealed a significant negative correlation between SspDHHC28A expression in S. spontaneum and sucrose content, suggesting a role in photosynthesis product transport during rapid growth. This study deepens our understanding of the DHHC gene family’s functional dynamics and evolutionary path in Saccharinae, laying a foundation for future research.